Are Donors Afraid of Charities' Core Costs? Scale Economies in Non-profit Provision and Charity Selection - Carlo Perroni; Ganna Pogrebna; Sarah Sandford; Kimberley Ann Scharf (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study contestability in non-profit markets when non-commercial providers supply a homogeneous collective good through increasing-returns-to-scale technologies. Unlike in the case of for-profit competition, in the non-profit case the absence of price-based sales contracts means that fixed costs are directly relevant to donors, and that they can translate into an entry barrier, protecting the position of an inefficient incumbent; or that, conversely, they can make it possible for inefficient newcomers to contest the position of a more efficient incumbent. Evidence from laboratory experiments show that fixed cost driven trade-offs between payoff dominance and perceived risk can lead to inefficient selection.
Keywords: L10; L30; D40; 330; not-for-profit organizations; entry; core funding